Self-efficacy and sexual offending against children: construction of a measure and changes following relapse prevention treatment - Pollock, Philip H. (Legal and criminological psychology, 1996)
The enhancement of self-efficacy beliefs is considered a pivotal aspect in the successful treatment of sex offenders and represents a central feature in the relapse prevention model of sexual crimes (Hall, 1989). The possible relationship between self-efficacy and recidivism has not been investigated. The paper describes a relapse prevention treatment study of 50 male sex offenders against children employing a new measure of self-efficacy which applies to sexual crimes. The test was constructed based on Kirsch's (1985) causal model of self-efficacy. The three subscales of the test represent: 1. demands of high-risk situations; 2. efficacy of coping skills and ability; 3. appreciation and expectation of rewards. Treatment outcome showed significant changes for the three self-efficacy test subscales. A preliminary analysis demonstrated that subscale 3 and the speed at which a coping response was produced accurately classified recidivist and non-recidivist participants at a three-year follow-up period. The findings suggest the importance of assessing self-efficacy beliefs when treating child sex offenders and their relevance to treatment is discussed.